Gamatun: Penggunaan Media Gamma AI dalam Pembelajaran Teks Pantun pada Siswa Kelas Vlll di SMPN 1 Galis Pamekasan - Ali, Anis Safira; Efendi, Agik Nur; Alatas, Mochamad Arifin (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The learning of pantun texts is often considered less interesting by students because it is delivered conventionally and lacks context. The presence of Gamma AI media aims to create a more interactive, visual, and character-aligned learning experience for today's students. The purpose of this research is to analyze the implementation and results of using Gamma AI media in the learning of Pantun Text for 8th-grade students at SMPN 1 Galis Pamekasan. This research uses a qualitative descriptive method. Data collection techniques included observation, interviews, and documentation. The results of the research on the use of Gamma AI media in learning pantun in the 8th grade at SMPN 1 Galis Pamekasan show a positive contribution to student engagement and understanding. Teachers were assisted in preparing and delivering the material, creating a more engaging learning atmosphere. This study concludes that the use of Gamma AI media successfully transformed the previously monotonous learning of pantun into a more engaging, imaginative, and meaningful learning process. Pembelajaran teks pantun sering kali dianggap kurang menarik oleh siswa karena disampaikan secara konvensional dan kurang kontekstual. Hadirnya media Gamma AI untuk menciptakan pengalaman belajar yang lebih interaktif, visual, dan sesuai dengan karakter siswa masa kini. Tujuan penelitian ini menganalisis pelaksanaan dan hasil dari penerapan media Gamma AI dalam Pembelajaran Teks Pantun pada Siswa Kelas Vlll di SMPN 1 Galis Pamekasan. Penelitian ini menggunakan metode dekriptif kualitatif. Teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Hasil penelitian Penggunaan media Gamma AI dalam pembelajaran pantun di kelas VIII SMPN 1 Galis Pamekasan memberikan kontribusi positif terhadap keterlibatan dan pemahaman siswa. Guru terbantu dalam menyusun dan menyampaikan materi, sehingga tercipta suasana belajar yang lebih menarik. Penelitian ini menyimpulkan bahwa penggunaan media Gamma AI berhasil mengubah pembelajaran pantun yang semula terkesan monoton menjadi proses belajar yang lebih menarik, imajinatif, dan penuh makna.